FITNESS Acts as a Negative Regulator of Immunity and Influences the Plant Reproductive Output After Pseudomonas syringae Infection - Mengarelli, Diego Alberto; Roldán Tewes, Lara; Balazadeh, Salma; Zanor, María Inés (Frontiers in Plant Science, 2021)
Plants, as sessile organisms, are continuously threatened by multiple factors and therefore their profitable production depends on how they can defend themselves. We have previously reported on the characterization of fitness mutants which are more tolerant to environmental stresses due to the activation of defense mechanisms. Here we demonstrate that in fitness mutants, which accumulate moderate levels of salicylic acid (SA) and have SA signaling activated, pathogen infection is restricted. Also, we demonstrate that NPR1 is essential in fitness mutants for SA storage and defense activation but not for SA synthesis after Pseudomonas syringae (Pst) infection. Additionally, these mutants do not appear to be metabolically impared, resulting in a higher seed set even after pathogen attack. The FITNESS transcriptional network includes defense-related transcription factors such as ANAC072, ORA59, and ERF1 as well as jasmonic acid (JA) related genes including LIPOXYGENASE2 (LOX2), CORONATINE INSENSITIVE1 (COI1), JASMONATE ZIM-domain3 (JAZ3) and JAZ10. Induction of FITNESS expression leads to the downregulation of COI1, and to an upregulation of JAZ3 and JAZ10. As COI1 loss of function abolishes JA-dependent responses and, JAZ3 and JAZ10 act as repressors of JA signaling, elevated FITNESS expression leads to JA insensitivity. Taken together, FITNESS plays a crucial role in the cross-talk between SA and JA during pathogen attack and allows a cost-efficient way to prevent undesirable developmental effects.